PROJECT-BASED TRAINING IN HIGHER MEDICAL EDUCATION - Maria R. Karpova; Sergey I. Karas (Высшее образование в России, 2022)
Federal state educational standards aim at formation of the students’ competences, whichare treated as an objective of learning. Development of students’ competencies takes place, in particular, in project-based training, which has been approved in a course of microbiology and in an interdisciplinary educational program for specialty “Medical cybernetics”. An interdisciplinary approach reveals the additional advantages of project-based education.